Pantry and Stored Food Pests - P.G. Koehler (EDIS)
This document provides an overview of pantry and stored food pests, detailing their biology, common species, and control methods. These pests, including flour beetles, grain moths, and weevils, infest various food items and can cause significant economic losses. The document emphasizes the importance of proper storage, regular inspections, and hygiene to prevent infestations. Control methods include discarding infested items, using heat or cold treatments, and applying insecticides. It highlights the need for thorough cleaning and sealing of food containers to manage and prevent pest problems effectively.